Response from the authors of the article "Critical review of the role of personal protective Equipment (PPE) in the prevention of risks related to agricultural pesticide use" to the letter to the editor from the European crop protection association (ECPA) Occupational and bystander exposure expert group (OBEEG). (June 2021) - Garrigou, A.; Laurent, C.; Baldi, I.; Berthet, A.; Colosio, C.; Daubas-Letourneux, V.; Galey, L.; Goutille, F.; Jackson Filho, J.-M.; Jas, N.; Jouzel, J.-N.; Judon, N.; et al.
Abstract: In March 2020, Safety Science published the article "Critical review of the role of PPE in the prevention of risks related to agricultural pesticide use" by an international group of researchers working for public research organisations. An expert group from an association representing the interests of the agricultural pesticide industry at European level (the European Crop Protection Association -ECPA-) then published a letter challenging the relevance of the discussion and the conclusions of this article. The authors of the review have decided to use their right to reply.